PARTISIPASI LEMBAGA DALAM PELAKSANAAN PENDIDIKAN SISTEM GANDA DI SEKOLAH MENENGAH KEJURUAN - BARKAH LESTARI (Universitas Negeri Yogyakarta, 2002)
Abstract The purpose of this study is to investigate the participation of the counterpart institutions I the implementation of the dual system education of the vocational high schools. The study was conducted at SMKN 7 Yogyakarta (The State Vocational High School 7 of Yogyakarta) . the subject were the school principle, the dual system education field coordinator, the counselor, the students, and the director as well as the instructors of the counterpart institution. The data were collected by the in-depth interview and the documentation sort. The data indicate that the counterpart institution has not been involved actively in the implementation of the dual system education. Keywords: dual system education, vocational high school, and counterpart institution participation.